Twelve tips for successfully implementing logbooks in clinical training - Schüttpelz-Brauns, Katrin; Narciß, Elisabeth; Obertacke, Udo (Medical teacher, 2016)
Background: Logbooks are widely used to set learning outcomes and to structure and standardize teaching in clinical settings. Experience shows that logbooks are not always optimally employed in clinical training. In this article, we have summarized our own experiences as well as results of studies into twelve tips on how to successfully implement logbooks into clinical settings.Methods: We conducted both a workshop concerning the importance of logbook training to exchange experiences in teaching practice, organization, didactic knowledge and a literature research to compare our own experiences and add additional aspects.Results: Tips include the process of developing the logbook itself, the change-management process, conditions of training and the integration of logbooks into the curriculum.Conclusions: Logbooks can be a valuable tool for training in clinical settings, especially when multiple sites are involved, when you take our tips into consideration.
Gesehen am 27.06.2019